A teacher unlike me: Social distance, learning, and intergenerational mobility in developing countries - Karachiwalla, Naureen (University of Chicago Press, 2019)
Same-type teachers are believed to improve the learning outcomes of disadvantaged students. This paper examines an understudied characteristic—caste—with rich longitudinal data from Pakistan to identify causal effects. The matching and switching of students to teachers is pseudorandom, and effects are not driven by unobserved teacher characteristics correlated with caste. Low-caste boys learn significantly more when taught by high-caste teachers. They have higher aspirations, and their parents spend significantly longer helping with homework when taught by these teachers. These results illustrate that, contrary to previous findings, different-type teachers may sometimes promote educational attainment and aspirations and, thus, intergenerational mobility.